Evaluation of PT HM Sampoerna Tbk's Financial Health through Financial Ratio Analysis: Implications for investors (2022 ”“ 2023) - Ersi, Elisabet -; Hermuningsih, Sri (Admisi dan Bisnis, 2025)
This research aims to evaluate the financial health of PT HM Sampoerna Tbk through financial ratio analysis for the years 2022 and 2023, and its implications for investors. The methodology includes an analysis of liquidity ratios, asset management effectiveness, funding structure, and profitability. The analysis results indicate an increase in the current ratio from 1.69 in 2022 to 1.72 in 2023, reflecting improved liquidity. The debt ratio also decreased from 0.49 to 0.46, signaling a reduced reliance on debt and enhanced financial stability. Although the accounts receivable turnover and asset turnover ratios experienced slight declines, both remain efficient and in line with good industry standards. Meanwhile, the cash turnover ratio saw a significant increase from 10.53 to 38.80, indicating greater efficiency in cash management. In terms of profitability, the profit margin, ROA, and ROE increased to 6.95%, 14.58%, and 27.00%, respectively, reflecting the company's effectiveness in managing costs and assets. Overall, this analysis demonstrates improved financial performance, providing positive signals for investors and enhancing the long-term growth prospects of PT HM Sampoerna Tbk as an attractive investment option